High-Resolution 3D Seismic Imaging of Fault Interaction and Deformation Offshore San Onofre, California - Holmes, James J.; Driscoll, Neal W.; Kent, Graham M. (Frontiers in Earth Science, 2021)
The Inner California Borderland (ICB) records a middle Oligocene transition from subduction to microplate capture along the southern California and Baja coast. The closest nearshore fault system, the Newport-Inglewood/Rose Canyon (NIRC) fault complex is a dextral strike-slip system that extends primarily offshore approximately 120 km from San Diego to Newport Beach, California. Holocene slip rates along the NIRC are 1.5-2.0 mm/yr in the south and 0.5 mm/yr along its northern extent based on trenching and well data. High-resolution 3D seismic surveys of the NIRC fault system offshore of San Onofre were acquired to define fault interaction across a prominent strike-slip step-over. The stepover deformation results in transpression that structurally controls the width of the continental shelf in this region. Shallow coring on the shelf yields a range of sedimentation rates from 0.27-0.28 mm/yr. Additionally, a series of smaller anticlines and synclines record subtle changes in fault trends along with small stepovers and secondary splay faults. Finally, sedimentary units onlapping and dammed by the anticline, place constraints on the onset of deformation of this section of the NIRC fault system. Thickness estimates and radiocarbon dating yield ages of 560,000 to 575,000 years before present for the onset of deformation.